KECEMASAN PASIEN PENYAKIT GINJAL KRONIS YANG MENJALANI HEMODIALISA - Devi Novita Damanik (Universitas Prima Indonesia, 2019)
Background: Anxiety is a condition of psychological and physiological disorders characterized by cognitive, somatic, emotional disturbances and components of behavioral sequences. Purpose: This study aims to describe the anxiety of chronic kidney disease patients undergoing hemodialysis. Methods: This study uses univariate analysis which will describe the anxiety level of chronic kidney disease patients undergoing hemodialysis. The anxiety variable was measured using the HARS (Hamilton Anxiety Rating Scale) anxiety instrument with a validity value of 0.68 dd 0.93 and a reliability value of 0.93. The population in this study were all chronic kidney disease patients who underwent hemodialysis and experienced anxiety. The sampling technique used in this study was purposive sampling technique. The sample in this study were patients with chronic kidney disease who met the requirements of the study patients, namely: Patients who underwent hemodialysis for less than one year, patients undergoing hemodialysis with femoral vein puncture, patients undergoing hemodialysis twice a week. Results: The results showed that the study respondents had a mild anxiety rate of 9 patients (56.25%), moderate anxiety as many as 8 patients (21.875%) and severe anxiety as many as 8 patients (21.875%). Conclusion: conclusions and implications for nursing practice. The results showed a high incidence of anxiety in patients undergoing hemodialysis and distributed evenly on mild, moderate and severe anxiety.